2018
DOI: 10.1186/s12933-018-0782-0
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular subclinical myocardial dysfunction in uncomplicated type 2 diabetes mellitus is associated with impaired myocardial perfusion: a contrast-enhanced cardiovascular magnetic resonance study

Abstract: BackgroundEarly detection of subclinical myocardial dysfunction in patients with diabetes mellitus (DM) is essential for recommending therapeutic interventions that can prevent or reverse heart failure, thereby improving the prognosis in such patients. This study aims to quantitatively evaluate left ventricular (LV) myocardial deformation and perfusion using cardiovascular magnetic resonance (CMR) imaging in patients with type 2 diabetes mellitus (T2DM), and to investigate the association between LV subclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 38 publications
8
49
2
1
Order By: Relevance
“…In our study, CMR-derived LV strains were similar among the three groups regardless of the presence of coexisting hypertension. We did not observe that a significantly decreased GLS in T2DM patients compared with normal subjects [30]. The above difference may lie in the duration of diabetes in the study populations.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In our study, CMR-derived LV strains were similar among the three groups regardless of the presence of coexisting hypertension. We did not observe that a significantly decreased GLS in T2DM patients compared with normal subjects [30]. The above difference may lie in the duration of diabetes in the study populations.…”
Section: Discussioncontrasting
confidence: 67%
“…The above difference may lie in the duration of diabetes in the study populations. Specifically, the mean duration of diabetes in the longerterm T2DM group was approximately 11 years in Liu's study [30], whereas the duration in our study was relatively short at only approximately 8 years. In this study, we also found that the LA strain changed significantly, indicating that LA deformation-related impairment could appear even earlier than the LV strain in the early stages of DCM, a finding that is consistent with Cameli's study [31].…”
Section: Discussioncontrasting
confidence: 64%
“…The main ndings of this study are as follows: 1 Similar to most progressive myocardial diseases, subendocardial bers are more vulnerable to being affected; thus, longitudinal contractile function representing as GLPS may be impaired earlier and more severely [8] , as shown in previous studies with hypertension [17,18] and T2DM [13,19] , as well as in our patients. In hypertension, there is insulin resistance and activation of the sympathetic nervous system and renin-angiotensin-aldosterone system, which may result in diffuse myocardial brosis [12] .…”
Section: Discussionsupporting
confidence: 54%
“…The increased resting myocardial perfusion in hypertension may re ect an adaptive mechanism, adapting to the increased oxygen demand for the heart to work under increased afterload [22,25] . In T2DM, increased resting myocardial perfusion has been exhibited in some previous studies [26][27][28] , while others have reported decreased resting perfusion [19,29] . This discrepancy may be due to different study populations, investigation modalities, and relatively modest sample sizes.…”
Section: Discussionmentioning
confidence: 83%
“…Although there is a strong association between CAC and incident HF, only partly mitigated after adjustment for cardiovascular risk factors, 7,8 it seems likely that this reflects the contribution of overt CAD to HF. Previous studies suggesting a link between CAC and LV dysfunction were in patients with very high burdens of CAC (≥400), 9 greater severity of LV dysfunction measured by ejection fraction, 10,11 or high baseline risk, such as those with suspected CAD or known diabetes 12,13 . The role of CAD in the development of SBHF is unclear in the setting of early disease.…”
Section: Introductionmentioning
confidence: 99%